From Theory to Practice: A Reflective Analysis of a Hotel Management Internship in a Japanese Resort - Phuyal, Aayousha (NPRC Journal of Multidisciplinary Research, 2025)
Background: Internships are a critical pedagogical component in hotel management education, serving to bridge theoretical knowledge with practical industry application. This report stems from a 12-month training internship at Angel Grandia Echigo Nakazato, a family-oriented resort in Japan, undertaken to gain immersive experience in operational hospitality departments.Objectives: The primary objectives were to acquire hands-on skills in Housekeeping and Food & Beverage Service, understand daily resort operations, apply customer service theory in practice, and analyze the resort’s strategic positioning within the competitive hospitality landscape.Methods: The internship followed a rotational training methodology. Qualitative data was gathered through direct participation, observational learning, and reflective practice across two key departments: Housekeeping (1 month, 20 days) and F&B Service (8 months). A situational analysis (SWOT) was conducted based on operational experience and organizational review.Findings: The internship facilitated significant development of technical and soft skills, including SOP adherence, inventory management, and guest interaction. Key challenges identified were language barriers, seasonal workload management, and maintaining service consistency. Participation in major seasonal events provided crucial insights into large-scale hospitality operations. A SWOT analysis revealed the resort’s strengths in family services and location, alongside weaknesses in facility maintenance and market diversification.Conclusion & Recommendation: The internship was a transformative experience that enhanced professional readiness and industry understanding. It is concluded that immersive, departmental training is essential for competency development. Recommendations for the resort include enhancing language support for international staff, diversifying market segments beyond families, and implementing a proactive digital maintenance system. For academic programs, pre-internship language preparation and structured reflective components are advised.Implementation: The findings can be implemented by hospitality educators to design more effective internship curricula, focusing on pre-departure preparation and reflective assessment. Resort management can apply the operational recommendations to improve staff training programs, guest experience, and strategic marketing initiatives.